The Effect of ESG-Based Financial Statement Transparency on Investor Confidence - Antony, Antony; Agustin, Lena (Pt. Anagata Sembagi Education, 2025)
The increasing demand for non-financial transparency has encouraged publicly listed companies to integrate Environmental, Social, and Governance (ESG) aspects into financial reporting as a basis for investment decision-making. However, the growing intensity of ESG reporting does not always translate into higher investor trust, raising empirical concerns regarding the effectiveness of ESG transparency. This study aims to empirically examine the effect of ESG-based financial reporting transparency on investor trust in the Indonesian capital market. A quantitative explanatory approach was employed, and data were analyzed using Partial Least Squares Structural Equation Modeling (SEM–PLS). The research sample comprised 132 firm-year observations of publicly listed companies that consistently published ESG reports. ESG transparency was measured using a disclosure index based on Global Reporting Initiative and Sustainability Accounting Standards Board standards, while investor trust was proxied by capital market indicators. The results indicate that ESG-based financial reporting transparency has a positive and statistically significant effect on investor trust. Partial analysis reveals that governance transparency exerts the strongest influence, followed by environmental and social dimensions. These findings demonstrate that investor trust is shaped by the quality and credibility of ESG disclosure rather than the mere existence of sustainability reports, and they confirm the relevance of signaling theory and information asymmetry reduction in explaining investor responses to ESG transparency.